Produits-terroirs-paysages et développement local dans les Alpes de Haute-Provence - Philippe Moustier (Belgeo)
The rural department of the Alpes de Haute-Provence has a variety of agro-terroirs allowing the cultivation of a wide range of agricultural productions. For about thirty years, the product-terroir-landscape triptych has become a local development issue. The promotion of productions through short circuits is important in this tourist department, at the gates of the Aix-Marseille-Provence metropolis. These productions also supply food companies and others in the field of cosmetics and perfumes. The cultivation of lavender-lavandin, whose products are little valued by short circuits, has become over the years an identity marker of these low-alpine landscapes, a source of attractiveness for tourism.